In vitro antitumor actions of extracts from endemic plant Helichrysum zivojinii - Matić Ivana Z; Aljančić Ivana; Žižak Željko; Vajs Vlatka; Jadranin Milka; Milosavljević Slobodan; Juranić Zorica D (BMC, 2013)
Abstract Background The aim of this research was to determine the intensity and mechanisms of the cytotoxic actions of five extracts isolated from the endemic plant species Helichrysum zivojinii Černjavski & Soška (family Asteraceae) against specific cancer cell lines. In order to evaluate the sensitivity of normal immunocompetent cells implicated in the antitumor immune response, the cytotoxicity of extracts was also tested against healthy peripheral blood mononuclear cells (PBMC). Methods The aerial parts of the plants were air-dried, powdered, and successively extracted with solvents of increasing polarity to obtain hexane, dichloromethane, ethyl-acetate, n-butanol and methanol extracts. The cytotoxic activities of the extracts against human cervix adenocarcinoma HeLa, human melanoma Fem-x, human myelogenous leukemia K562, human breast adenocarcinoma MDA-MB-361 cells and PBMC were evaluated by the MTT test. The mode of HeLa cell death was investigated by morphological analysis. Changes in the cell cycle of HeLa cells treated with the extracts were analyzed by flow cytometry. The apoptotic mechanisms induced by the tested extracts were determined using specific caspase inhibitors. Results The investigated Helichrysum zivojinii extracts exerted selective dose-dependent cytotoxic actions against selected cancer cell lines and healthy immunocompetent PBMC stimulated to proliferate, while the cytotoxic actions exerted on unstimulated PBMC were less pronounced. The tested extracts exhibited considerably stronger cytotoxic activities towards HeLa, Fem-x and K562 cells in comparison to resting and stimulated PBMC. It is worth noting that the cytotoxicity of the extracts was weaker against unstimulated PBMC in comparison to stimulated PBMC. Furthermore, each of the five extracts induced apoptosis in HeLa cells, through the activation of both intrinsic and extrinsic signaling pathways. Conclusion Extracts obtained from the endemic plant Helichrysum zivojinii may represent an important source of novel potential antitumor agents due to their pronounced and selective cytotoxic actions towards malignant cells.